From COVID-19 to Cancer mRNA Vaccines: Moving From Bench to Clinic in the Vaccine Landscape - Chakraborty, Chiranjib; Sharma, Ashish Ranjan; Bhattacharya, Manojit; Lee, Sang-Soo (Frontiers in Immunology, 2021)
Recently, mRNA vaccines have become a significant type of therapeutic and have created new fields in the biopharmaceutical industry. Presently, mRNA vaccines are promising next-generation vaccines that have introduced a new age in vaccinology. Recent approval of two COVID-19 mRNA vaccines (mRNA-1273 and BNT162b2) has accelerated mRNA vaccine technology and boosted the pharmaceutical and biotechnology industry. These mRNA vaccines will help to tackle this pandemic through immunization, offering considerable hope for future mRNA vaccines. Human trials with data from both mRNA cancer vaccines and mRNA infectious disease vaccines have provided encouraging results, inspiring the pharmaceutical and biotechnology industries to focus on this area of research. In this article, we discuss current mRNA vaccines broadly in two parts. In the first part, we discuss mRNA vaccines in general and COVID-19 mRNA vaccines. We presented the mRNA vaccine structure in general, the different delivery system, the immune response, and the recent clinical trials for mRNA vaccines (both for cancer mRNA vaccines and different infectious diseases mRNA vaccines). In the second part, different COVID-19 mRNA vaccines were explained. Finally, we illustrated a snapshot of the different leading mRNA vaccine developers, challenges, and future prospects of mRNA vaccines.